2013
DOI: 10.7150/ijbs.5855
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Prostate Cancer Stem-Like Cells from Human Prostate Cancer Cell Lines by Culture in Serum-Free Medium and Chemoradiotherapy

Abstract: The discovery of rare subpopulations of cancer stem cells (CSCs) has created a new focus in cancer research. As CSCs demonstrate resistance to chemoradiation therapy relative to other cancer cells, this allows the enrichment of CSC populations by killing apoptosis-susceptible cancer cells. In this study, three commonly used human prostate cancer (PCa) cell lines (DU145, PC-3 and LNCaP) were examined for their expression of the putative stem cell markers CD133 and CD44 via flow cytometric analysis. Under normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 29 publications
(34 reference statements)
11
76
0
Order By: Relevance
“…Al-Assar et al (88) reported that breast CSCs in xenografts exposed to radiation were enriched, as demonstrated by an increased number of CD24 − /epithelial-specific antigen + cancer cells, a marker of breast CSCs, in xenografts. The enrichment of breast CSCs in xenografts exposed to radiation was also considered as the result of different radioresistance between CSCs and adult cancer cells, which was consistent with the aforementioned speculation of Wang et al (87). This explanation was undoubtedly reasonable, but may be not complete.…”
Section: Radiation Induces the Generation Of Cscssupporting
confidence: 86%
See 2 more Smart Citations
“…Al-Assar et al (88) reported that breast CSCs in xenografts exposed to radiation were enriched, as demonstrated by an increased number of CD24 − /epithelial-specific antigen + cancer cells, a marker of breast CSCs, in xenografts. The enrichment of breast CSCs in xenografts exposed to radiation was also considered as the result of different radioresistance between CSCs and adult cancer cells, which was consistent with the aforementioned speculation of Wang et al (87). This explanation was undoubtedly reasonable, but may be not complete.…”
Section: Radiation Induces the Generation Of Cscssupporting
confidence: 86%
“…It has been demonstrated that CSCs can be enriched both in vitro and in vivo by radiation, which indicates the possibility of radiation-induced generation of CSCs. Wang et al (87) demonstrated that the proportion of prostate cancer stem-like cells in a human prostate cancer cell culture increased significantly following exposure to radiation. The authors postulated that radiation eliminated the radiosensitive adult cancer cells in the culture by inducing apoptosis, which resulted in the enrichment of radioresistant CSCs.…”
Section: Radiation Induces the Generation Of Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovarian cancer cell lines, enrichment of CSCs was found in response to either cisplatin or paclitaxel or combination of both [51]. Similar results were reported in pancreatic cancer [44, 52], glioblastoma [53] and prostate cancer [54]. In our previous work, the combination of paclitaxel and serum-free medium cultivation enriched CSCs in lung adenocarcinoma A549 cells [55].…”
Section: Icscs Driven By Radio-chemotherapysupporting
confidence: 72%
“…The serum-free suspension culture method is based on supplementation of culture medium with growth factors to promote proliferation of undifferentiated cells, concomitantly with the elimination of differentiated cells. In recent years, this approach has been used to isolate many kinds of CSCs including prostate [20], retinal [21], and prostate [22] cancer stem cells. Serum-free suspension culture may allow isolation and culture of choriocarcinoma stemlike cells (CSLCs) from human choriocarcinoma cell lines.…”
mentioning
confidence: 99%